The Effect of Natural Feeding on The Gowth of Comet Fish (Carassius auratus) - Mauludin, Muhammad Rizki; Firmani, Ummul; Rahim, Andi Rahmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Indonesia's ornamental fish has a high export potential. Indonesia occupies the second position in the world for ornamental fish exports. One type of fish that can be exported is Comet Fish (Carrassius auratus). This study aims to determine whether feeding silk moss, daphnia, silk worms, and pellets has an effect on daily length and weight and absolute length and weight. Furthermore, this study aims to determine which type of natural food is best for the growth of comet fish fry. The treatments in this study used were pellets, moss, daphnia, and silk worms. The parameters observed were daily length and weight rate and absolute weight and length. And water quality. The results of this study showed the highest daily weight growth rate with a value of 1.63 ± 0.07 g / day. In daily length growth treatment C showed the highest results with a value of 3.94 ± 0.08 cm/day. In the calculation of absolute weight treatment C showed the best results with a value of 0.32 ± 0.02 g. In the calculation of the absolute length of treatment C showed the highest results of 0.32 ± 0.02 cm. Water quality measured is ph and temperature each showed numbers in the range of 25.7-27.6 oC, and pH 7.3-8.3.